OPERATIONAL MANAGEMENT ANALYSIS IN OPTIMIZING CHITOSAN FERTILIZER PRODUCTION BASED ON SWIMMING CRAB SHELL WASTE AT THE CANGKANG SALONA GROUP, LOKTUAN VILLAGE - Indriani; Suriyanti; Ramlawati (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the implementation of operational management in the production of chitosan fertilizer based on swimming crab shell waste at the Cangkang Salona Group, Loktuan Village, Bontang City. The research uses a descriptive qualitative approach with a case study method, through observation, in-depth interviews, and documentation analysis. The results show that aspects of operational management such as production planning, raw material management, production processes, and cost control have not been implemented optimally. The main constraints are limited human resource capacity in cost accounting, simple production technology, and irregular supply chains. However, this business has great potential in supporting sustainable agriculture and local community empowerment. Recommendations given include the implementation of structured production planning, continuous training on production cost calculation, implementation of simple digital recording systems, and strengthening partnerships with external parties. The implementation of these recommendations is expected to improve operational efficiency, business sustainability, and positive impacts on the local economy.